Financing Education Utility Products in Islamic and Traditional Banks - Al-Darabseh, Wesal Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
Recently, several Islamic banks established programs to finance education utility products to give the opportunity to individuals to continue their education and to qualify them to serve their country. In this study, we examined the current educational utilities that are financed by Islamic banks and the contracts that are utilized to finance them. In addition, educational utilities financing programs in Islamic banks were compared to the ones that are implemented in the traditional banks. The study used the descriptive approach and included more than 10 Islamic banks and several traditional ones from different countries.The study revealed that Tawarruq, Murabaha and Ijara are the major contracts used for financing educational utilities in the Islamic banks. In addition, the education utility's that are financed in the Islamic banks are limited and do not cover living expenses of the students and studying abroad. Based on the results, the study suggests for the Islamic banks to finance training courses, workshops, and other educational activities and to benefit from the experience of traditional banks, especially American ones, in financing educational utilities such as covering living expenses and postponing the loan until student graduation after obeying them to rules of Islamic Sharia.
Keywords: reality; finance; Education benefits; Islamic banks; conventional banks; A comparative study